1993
DOI: 10.1136/jnnp.56.9.993
|View full text |Cite
|
Sign up to set email alerts
|

Exercise performance and fatiguability in patients with chronic fatigue syndrome.

Abstract: To exanine the role of delay in recovery of peripheral muscle function following exercise in the fatigue experienced by patients with the chronic fatigue syndrome (CFS) and to examine the influence of effort perception in limiting exercise performance in these patients, a study was carried out on a group of twelve patients with chronic fatigue syndrome and 12 sex and age-matched sedentary control subjects. Symptom limited incremental cycle exercise tests including measurements of perceived exertion were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 25 publications
6
64
0
Order By: Relevance
“…But, why is there an increased sensation of effort and evidence from recording of heart rate to suggest an excessive central activation (Riley et al 1990 ;Lloyd et al 1991) in the early stages of exercise ? Heart rate only falls later in activation (Riley et al 1990 ;Gibson et al 1993). We need more evidence on the effects of the common antecedents of CFS upon motor processes.…”
Section: The Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…But, why is there an increased sensation of effort and evidence from recording of heart rate to suggest an excessive central activation (Riley et al 1990 ;Lloyd et al 1991) in the early stages of exercise ? Heart rate only falls later in activation (Riley et al 1990 ;Gibson et al 1993). We need more evidence on the effects of the common antecedents of CFS upon motor processes.…”
Section: The Hypothesismentioning
confidence: 99%
“…We are impressed that patients' reports of fatigue and muscle weakness are complemented by neurophysiological investigations that have consistently demonstrated normal muscular strength but an increased perception of effort on both isometric contraction (Lloyd et al 1991 ;Kent-Braun et al 1993) and isotonic exercise (Riley et al 1990 ;Gibson et al 1993 ;Sisto et al 1996). The sense of effort is an important concept for motor physiology.…”
Section: The Hypothesismentioning
confidence: 99%
“…These include studies of subjects with CFS as defined in the UK [45,46], with immune dysfunction as seen in Australia [47], with CFS as defined in the USA [48], and with post Epstein Barr virus fatigue syndrome [49]. There is also no objective evidence of a delayed appearance of abnormal post exertional muscle fatigability [50,51], as is sometimes claimed. Furthermore, the pattern of physical and mental fatigability encountered does not correspond with that found in neuromuscular disorders [52,53].…”
Section: The Pathophysiology Of Fatigue In Cfsmentioning
confidence: 99%
“…There is no consensus regarding the appropriate exercise prescription for patients with CFS. Some investigators [2][3][4][5] have reported that continuous exercise of sufficient intensity and duration exacerbates symptoms in patients with CFS. Sisto et al, 9 however, demonstrated that a discontinuous graded exercise test did not greatly exacerbate the underlying illness of patients with CFS.…”
mentioning
confidence: 99%
“…[2][3][4][5] As a result, patients with CFS tend to limit their physical activity in order to minimize symptoms. [2][3][4][5] The Surgeon General has suggested that moderate aerobic exercise (eg, brisk walking) performed for 30 minutes, 3 times each week, will convey considerable health benefits and subsequently improve quality of life in individuals without functional limitations. 7 Additional research has demonstrated that people do not have to perform 30 minutes of continuous exercise to receive such health benefits.…”
mentioning
confidence: 99%